Current Practice of Using Technology in Health-care Delivery in Saudi Arabia: Challenges and Solutions - Ahmed, Nehad J. (Asian Journal of Pharmaceutics (AJP), 2021)
The use of technology in delivering health-care services in Saudi Arabia is a significant step to take. Several application systems were implemented now in Saudi Arabia and provide medical services. This paper explores the current practice of using technology in health-care delivery in Saudi Arabia and brought to light the impact of technologies in health-care delivery on patients and their reported barriers. This is a narrative review which was conducted of published articles as well as gray literature on the application of technology in delivering medical care. Studies that met the following criteria were included: Addressed a relevant aspect of technology in health-care delivery; written in English; published between 1994 and June 2020; qualitative and quantitative study designs, systematic reviews, and primary and secondary research. The findings reveal evidence that utilizing technologies in delivering health services in Saudi Arabia are growing; however, it remains low. It has been found that inadequate infrastructure, lack of awareness of the importance of these technologies, shortage of professionals, lack of an information management plan, lacking a national plan for medical data exchange, and lacking a national regulator were among the main barriers. To achieve greater acceptance and use of technologies to deliver health-care services in our region, health workers should ensure that the services provided reflect as closely as possible local services and that social and religious culture is taken into account in the community. The findings of this study are also valuable for governments, organizations, and health policymakers to develop plans and policies to enhance the use of technology in delivering health-care services in Saudi Arabia.